Reframing HIV care: putting people at the centre of antiretroviral delivery. Issue 4 (16th February 2015) - Duncombe, Chris; Rosenblum, Scott; Hellmann, Nicholas; Holmes, Charles; Wilkinson, Lynne; Biot, Marc; Bygrave, Helen; Hoos, David; Garnett, Geoff
Summary The delivery of HIV care in the initial rapid scale‐up of HIV care and treatment was based on existing clinic‐based models, which are common in highly resourced settings and largely undifferentiated for individual needs. A new framework for treatment based on variable intensities of care tailored to the specific needs of different groups of individuals across the cascade of care is proposed here. Service intensity is characterised by four delivery components: (i) types of services delivered, (ii) location of service delivery, (iii) provider of health services and (iv) frequency of health services. How these components are developed into a service delivery framework will vary across countries and populations, with the intention being to improve acceptability and care outcomes. The goal of getting more people on treatment before they become ill will necessitate innovative models of delivering both testing and care. As HIV programmes expand treatment eligibility, many people entering care will not be 'patients' but healthy, active and productive members of society 1. To take the framework to scale, it will be important to: (i) define which individuals can be served by an alternative delivery framework; (ii) strengthen health systems that support decentralisation, integration and task shifting; (iii) make the supply chain more robust; and (iv) invest in data systems for patient tracking and for programme monitoring and evaluation.